Viable system dynamics intelligent framework for assessing and optimizing systemic reengineering for e-governance environments: A case study in corfu sunspots tourist agency - Assimakopoulos, Nikitas A.; Miaris, Alexandros (Acta Europeana Systemica, 2020)
Dealing with problems in complex environments that impede organizational cohesion, information dissemination and coordination is extremely difficult nowadays. Usage of technology without sophisticated information sharing planning and solid processes that serve with a bottom-up approach the needs of each individual within an organization, undermines time, cost and quality of deliverables. The eG4M (e-Government for Mediterranean Countries)project basically concentrates on extending, completing and improving the e-Model through the achievement of new research results and its application by participating with the support of the Mediterranean Countries (MCs) – in establishing and consolidating their e-Government systems. This paper focuses on the development of a generic system dynamics model that illustrates the behavior of e-governance systems based on the VSM (Viable Systems Model) as well as the development of a web, collaborative intelligent framework that is built upon the system dynamics model. The framework is meant to have the form of a web-based simulation that is able to identify critical issues related to product, customer, information sharing and service quality using visualizations, automated analytics and impact analysis delivered with natural language format to support the systemic reengineering process, mitigate risk, predict issues during the planning phase and help the user understand complexity and inform his decisions with predictive insights. Modeling the behavior of an e-governance system and being able to automatically process complex relationships, data and issues upon this system mitigates uncertainty at all levels, increases awareness and understanding of the real world and delivers sustainability and viability, increases growth and sets the basis for process autonomy and better coordination, controls and quality of deliverables.